MENERAPKAN GROUNDED THEORY KATHY CHARMAZ DALAM STUDI HADIS TEMATIK: STUDI KASUS HADIS PENTINGNYA PENDIDIKAN DI MASJID AT-TAQWA KP. SUKARELA DS. PULO PANJANG - Raja Khafizh Budiman; Hikmatul Luthfi; Muhammad Alif (MAHABBAH: Jurnal Ilmu Ushuluddin Dan Pemikiran Islam, 2026)
This research discusses the application of Grounded Theory by Kathy Charmaz in the study of education based on hadith, focusing on the roles of parents, teachers, and the community. Using a qualitative approach, this study explores how the educational values in hadith are implemented within the community at Masjid At-Taqwa, Kampung Sukarela, Pulo Panjang Village, Serang Regency. Data were collected through in-depth interviews and observations, revealing that the synergy among these three elements is crucial for creating a conducive learning environment. Parents serve as the primary educators instilling religious and moral values, while teachers act as facilitators who ease the learning process. The community supports education by fostering a learning culture and providing assistance to families. Findings indicate that active involvement from all parties can enhance educational quality and raise awareness of the importance of knowledge in daily life. This research aims to provide new insights into the application of educational values in a local context and encourage the community to be more active in seeking knowledge, thus producing individuals who are not only knowledgeable but also morally upright.